Party support for post-exceptionalism in agri-food politics and policy: Germany and the United Kingdom compared - Tosun, Jale (Journal of European public policy, 2017)
The past few years have witnessed the emergence of new actors and ideas in agri-food politics discussed under the heading ‘post-exceptionalism’. Yet our knowledge about which political actors promote a shift from exceptionalism toward post-exceptionalism is limited. How supportive are political parties of post-exceptionalism? Which political parties support a strong form for post-exceptionalism and which a weak one? To examine these research questions, the study concentrates on Germany and the United Kingdom. It shows that the green parties in Germany and the United Kingdom are the strongest advocates of opening up policy-making in the agri-food sector to new actors and of proposing policies that span across the boundaries of this policy sector. Parties that are more closely aligned with farmers’ interests tend to support weaker forms of post-exceptionalism. What also matters for explaining the parties’ positions on post-exceptionalism is how strongly they support state intervention in the economy.
Gesehen am 17.07.2017